2011
DOI: 10.1136/gut.2011.239301.81
|View full text |Cite
|
Sign up to set email alerts
|

Mortality following blood transfusion for non-variceal upper gastrointestinal bleeding

Abstract: Introduction Blood transfusion is integral to the management of non-variceal upper gastrointestinal bleeding (NV-UGIB), but its safety is being questioned in less severe cases. We, therefore aimed to measure 30-day and 2-year mortality after blood transfusion for NV-UGIB. Methods This was an observational analysis using routinely collected data at a single hospital in southwest Scotland affi liated to Glasgow University. Cox proportional hazards models were used to estimate the effect of blood transfusion on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 0 publications
3
21
0
Order By: Relevance
“…Even though transfusion might have a negative influence on survival within the first few months, it is not self-evident that transfusion has an impact on long-term survival. To our knowledge, only one previous study has indicated that treatment with blood transfusion increases long-term mortality in patients with non-variceal upper gastrointestinal bleeding [15]. This study was, however, retrospective and characterized by inclusion of heterogeneous bleeding sources with diverting prognosis (PUB, erosive esophagitis, malignancy).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Even though transfusion might have a negative influence on survival within the first few months, it is not self-evident that transfusion has an impact on long-term survival. To our knowledge, only one previous study has indicated that treatment with blood transfusion increases long-term mortality in patients with non-variceal upper gastrointestinal bleeding [15]. This study was, however, retrospective and characterized by inclusion of heterogeneous bleeding sources with diverting prognosis (PUB, erosive esophagitis, malignancy).…”
Section: Discussionmentioning
confidence: 67%
“…This is thought to be caused by an immunosuppressive effect of blood transfusion [12,13], which is believed to last for several years. Treatment with blood transfusion during or after coronary artery bypass surgery seems to reduce the long-term survival [14], and a similar finding has been reported for non-variceal upper gastrointestinal bleeding [15].…”
Section: Introductionmentioning
confidence: 75%
“…The work took place between 1 January 2008 and 31 December 2009 at University Hospital Crosshouse, Scotland (box 1). This work is part of our ongoing programme that investigates the epidemiology and management of upper GI bleeding 9 10…”
Section: Methodsmentioning
confidence: 99%
“…Patients who have endoscopic evidence of a portal hypertensive cause for their upper GI bleed (oesophageal varices, gastric varices or portal hypertensive gastropathy) were excluded from further analysis. Causes of NVGIB included gastric or duodenal ulcers or erosions, erosive gastritis, Mallory-Weiss lesions, erosive oesophagitis, idiopathic angiodysplasia and UGI tract tumours and malignancies 9 10. Patients with normal oesophago-gastro-duodenoscopy (OGD) following haematemesis would undergo angiography using CT if their bleeding persists and remains unexplained.…”
Section: Methodsmentioning
confidence: 99%
“…All patients who had significant morbidity have had received either Packed Cells or Fresh Frozen Plasma. In a study of Taha et al on blood transfusion 25 in patients with moderately severe Nonvariceal UGIB, mortality was higher, following blood transfusion. Whether this reflects selection bias, or an effect of co-morbidity or an effect of transfusion necessitates further studies.…”
Section: Discussionmentioning
confidence: 99%